Pharmacogenetic Approaches to Optimize Bioequivalence Studies in Generic Drug Development - Bae, Jihyun; Shon, Jihong; Kim, Myong‐Jin; Li, Karen (Journal of clinical pharmacology, 2025)
Given the significant impacts of interindividual genetic variability on drug safety and pharmacokinetics, integrating pharmacogenetic (PGx) considerations into pharmacokinetic (PK) bioequivalence (BE) study design can improve subject safety and data robustness in generic drug development. While PGx information has been often utilized in new drug development, its use in generic drug development has not been fully considered. To understand the current landscape of its utility in generic drug development, product‐specific guidances (PSGs) from the US Food and Drug Administration (FDA) containing PGx information were reviewed, along with study protocols submitted by generic drug applicants under abbreviated new drug applications (ANDAs) or controlled correspondences for the identified reference listed drugs (RLDs). Fifteen PSGs (15 RLDs) recommended PGx information as a consideration factor for subject population selection, particularly for drugs associated with inherited enzyme deficiencies or cytochrome P450 polymorphism. The PGx‐based considerations in these PSGs aimed to prevent serious adverse events (60%), optimize PK BE study design (7%), or address both factors (33%). Among the 15 RLDs, 5 had submitted ANDAs or correspondences with PK BE study protocols after their respective PSGs were published. Most of these submissions aligned with the PSG recommendations, incorporating PGx‐related exclusion criteria. These findings suggest that while the number of submissions is low, generic drug developers are increasingly integrating PGx considerations in PK BE studies, recognizing its potential to enhance safety and efficiency in generic drug development. Continuing efforts from both regulators and industry are critical to expand its application to other drug candidates.